Microsatellite loci variability in apple cultivars developed at VIR - A. V. Shlyavas; A. A. Trifonova; I. S. Chepinoga; A. S. Sidnin; K. V. Boris (Труды по прикладной ботанике, генетике и селекции)
Background. Microsatellite (SSR) markers are now widely used both for studying genetic diversity in fruit crop collections, including apple (Malus × domestica Borkh.), and for genotyping individual accessions. The apple collection held by VIR, being the largest in Russia, contains cultivars bred at five experiment stations of VIR. These cultivars not only meet the requirements of horticulture in the region of their origin, but also are interesting as sources of valuable traits for breeding programs. However, these cultivars have not previously been studied using microsatellite markers. Materials and methods. A set of 10 SSR markers (CH02c02b, CH03d01, CH01f03b, CH02d08, CH02c02a, CH05e03, CH02c09, CHVf1, CH01h01, COL) was used for genotyping 35 apple cultivars developed at VIR and four parental forms. Fluorescently labeled PCR products were separated by capillary electrophoresis on ABI Prism 3130xl.Results. In 35 apple cultivars from VIR, 97 alleles were identified at ten studied loci. The number of alleles per locus varied from 5 (CH02c02b) to 17 (CH02c02a). The frequency of unique alleles was 26,8%, with 12,4% for rare alleles. Polymorphism information content (PIC) values varied from 0,49 (CH02c02b) to 0,91 (CH02c02a) and averaged 0,76. Expected and observed heterozygosity levels averaged 0,79 and 0,56, respectively. Cluster analysis did not reveal a clear division of cultivars according to the place of origin (experiment stations of VIR), but revealed clustering according to pedigrees.Conclusion. A high level of polymorphism was observed in 35 apple cultivars from VIR using ten SSR markers. The obtained data on the allelic composition of the studied cultivars can be used for their identification and contribute to more efficient collection  management. Further studying and SSR genotyping of VIR’s apple collection and comparison with the data obtained in the presented work can help to identify the origin of cultivars with unknown pedigrees.